2016
DOI: 10.1016/j.jcrs.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the visual performance and quality of vision with combined symmetrical inferonasal near addition versus inferonasal and superotemporal placement of rotationally asymmetric refractive multifocal intraocular lenses

Abstract: None of the authors has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Neuroadaptation occurs after multifocal IOL implantation 8 ; therefore, this study sought to compare the 2 IOLs 12 months after implantation to allow for neuroadaptation. A study by McNeely et al 14 found that bilateral implantation of asymmetric multifocal IOLs with a combination of superotemporal placement of the near segment in the dominant eye and inferonasal placement of the near segment in the fellow eye yielded enhanced quality of vision compared with bilateral inferonasal placement. Another study 16 found that the placement of the near segment had no significant effect on visual performance; however, the numbers in this study were too small.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroadaptation occurs after multifocal IOL implantation 8 ; therefore, this study sought to compare the 2 IOLs 12 months after implantation to allow for neuroadaptation. A study by McNeely et al 14 found that bilateral implantation of asymmetric multifocal IOLs with a combination of superotemporal placement of the near segment in the dominant eye and inferonasal placement of the near segment in the fellow eye yielded enhanced quality of vision compared with bilateral inferonasal placement. Another study 16 found that the placement of the near segment had no significant effect on visual performance; however, the numbers in this study were too small.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with larger pupils may experience glare and halos after multifocal IOL implantation. [ 78 79 80 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 79 ] Astigmatic correction is mandatory to ensure good multifocal IOL results. As such, patients with irregular astigmatism are not good candidates for a multifocal IOL[ 78 80 ] since its correction is neither easy nor predictable. Further studies are needed to determine the visual effects of multifocal IOLs in patients with a history of previous refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To reach good visual results, the correct positioning of the distance and near segment is indispensable. For example, the cited paper demonstrates that a combination of a superotemporal position of the near segment in one eye and inferonasal in the other eye seems to increase visual quality [67]. A good method of assessing the performance of presbyopia-correcting IOLs is defocus curve testing [68] (Fig.…”
Section: Multifocal Iolsmentioning
confidence: 99%